HYBRID POWER GENERATION SYSTEM AND ENERGY-INDEPENDENT HYDROGEN-ELECTRICITY HYBRID CHARGING STATION, WHICH USE REVERSE ELECTRODIALYSIS DEVICE CAPABLE OF EFFICIENTLY PRODUCING HYDROGEN-ELECTRICITY - KIM, Han Ki; HAN, Ji-Hyung; JEONG, Namjo; KIM, Chan-Soo; HWANG, Kyo Sik (2018)
A hybrid power generation system comprises a reverse electrodialysis device and a fuel cell. When electricity is generated in the reverse electrodialysis device and hydrogen is simultaneously generated by a water decomposition reaction, the generated hydrogen is supplied to the fuel cell such that electricity is produced by an electrochemical reaction of hydrogen and oxygen in the fuel cell. Un système de production d'énergie hybride comprend un dispositif d'électrodialyse inverse et une pile à combustible. Lorsque de l'électricité est produite dans le dispositif d'électrodialyse inverse et que de l'hydrogène est généré simultanément par une réaction de décomposition d'eau, l'hydrogène généré est fourni à la pile à combustible de telle sorte que de l'électricité est produite par une réaction électrochimique d'hydrogène et d'oxygène dans la pile à combustible. 하이브리드 발전 시스템은 역전기투석 장치 및 연료전지를 포함한다. 역전기투석 장치에서 전기를 생산함과 동시에 물 분해 반응에 의한 수소를 생산하면, 생T성된 수소는 연료전지로 공급되어 연료전지에서 수소와 산소의 전기화학 반응에 의해 전기를 생산한다.